Influence Capital Adequacy Ratio and Loan to Deposit Ratio to The Company's Stock Price Bankings Listed On BEI - Thezar Fiqih Hidayat Hasibuan, Riza Fanny Meutia (Pusdikra Publishing, 2021)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) to the Share Price. The object of this research is 44 banking companies listed on the Indonesia Stock Exchange from 2014-2018. Samples were selected using the methodpurposive sampling namely 25 companies. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that the variableCapital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) does not have a direct effect on the Stock Price variable